3D CRANE SYSTEM - Mustafa, Umi Hani (Universiti Teknologi Petronas, 2004)
This is a research and analysis project on studying the 3D Crane System. The 3D Crane System is widely used for industrial purposes to move cargo, goods and supplies. But one of the problems is when the payload/pendulum is swinging too oscillatory. Thus, it could give the impact on the safety of personnel who controlling the crane and public servant around the crane area. The goals of this project are to analyse and study the dynamic behavior of 3D Crane System and to design and test a control strategy to improve the performance of the crane system. Through this project, the performance of the crane system is measured in terms of stability of the crane especially on the pendulum oscillation and accuracy of the crane movement to the desired position. In this project, only one control strategy had been designed, which is tuning the PID controller parameters. Thus, tuning the PID parameters expected to reduce the oscillatory of the payload and improving the performance of the crane system. Some tuning methods analysis had been used in order to obtain the tuning parameters of PID controller which are Ziegler Nichols Method and Ciancone Correlations Tuning Method. To obtain the PID tuning parameters, many experiments had been done by varying the gain to obtain the best response (constant amplitude). From the response, using the tuning method, the tuning parameters for PID controller is obtained. All the tuning parameters for each axis obtained were set into respective PID controller and combined it into 3 axis controller. The final response shows the response from actual cart position from 3 axis and response of angle payload in x and y axis. Conclude that, the objective of this project is met where the performance of the response of cart position and angle of payload is better compare before undergoing the tuning PID controller. The scopes of this project include literature review on 3D crane system and Matlab simulation by varying PID tuning parameters. The purpose of this simulation is to see the response curve based on tuning parameters obtained and compare with the response curve before the PID is tuned. Therefore, the performance of the crane system can be observed either better or not.